A Hybrid Evaluation-Optimization Trial to Evaluate an Intervention Targeting the Intersection of Alcohol and Sex in College Students and Simultaneously Test an Additional Component Aimed at Preventing Sexual Violence. Issue 12 (11th March 2021) - Tanner, Amanda E; Guastaferro, Kate M; Rulison, Kelly L; Wyrick, David L; Milroy, Jeffrey J; Bhandari, Sandesh; Thorpe, Shemeka; Ware, Samuella; Miller, Alicia M; Collins, Linda M
Abstract: Background: Using the multiphase optimization strategy (MOST), we previously developed and optimized an online behavioral intervention, itMatters, aimed at reducing the risk of sexually transmitted infections (STI) among first-year college students by targeting the intersection of alcohol use and sexual behaviors. Purpose: We had two goals: (a) to evaluate the optimized itMatters intervention and (b) to determine whether the candidate sexual violence prevention (SVP) component (included at the request of participating universities) had a detectable effect and therefore should be added to create a new version of itMatters . We also describe the hybrid evaluation-optimization trial we conducted to accomplish these two goals in a single experiment. Methods: First year college students ( N = 3, 098) at four universities in the USA were individually randomized in a hybrid evaluation-optimization 2 × 2 factorial trial. Data were analyzed using regression models, with pre-test outcome variables included as covariates in the models. Analyses were conducted separately with (a) immediate post-test scores and (b) 60-day follow-up scores as outcome variables. Results: Experimental results indicated a significant effect of itMatters on targeted proximal outcomes (norms) and on one distal behavioral outcome (binge drinking). There were no significant effects on other behavioral outcomes, including the intersection of alcohol and sexual behaviors. In addition, there were mixed results (positive short-term effect; no effect at 60-day follow-up) of the SVP component on targeted proximal outcomes (students' self-efficacy to reduce/prevent sexual violence and perceived effectiveness of protective behavioral strategies). Conclusions: The hybrid evaluation-optimization trial enabled us to evaluate the individual and combined effectiveness of the optimized itMatters intervention and the SVP component in a single experiment, conserving resources and providing greatly improved efficiency. Trial Registration: NCT04095065. Abstract : College freshmen who completed an optimized online intervention, itMatters, showed greater reductions in alcohol and sex-related norms and binge drinking than those who did not.